A Costly Commitment: Populism, Government Performance, and the Quality of Bureaucracy - Luca Bellodi; Massimo Morelli; Matia Vannoni (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the consequences of populism for government performance and the quality of bureaucracy. When voters lose trust in representative democracy, populists strategically supply unconditional policy commitments that are easier to monitor for voters. When in power, populists implement their policy commitments regardless of financial constraints and expert assessment of the feasibility of their policies, worsening government performance and dismantling resistance from expert bureaucrats. We use novel data on about 8,000 municipalities in Italy, over a period of 20 years, and we estimate the effect of electing a populist mayor with a close-election regression discontinuity design. We find that the election of a populist mayor leads to more debts, a larger share of procurement contracts with cost overruns, higher turnover among top bureaucrats, and a sharp decrease in the percentage of graduate bureaucrats. These results contribute to the literature on populism, government performance, and bureaucratic appointments.
Keywords: 330; populism; government performance; bureaucracy; turnover